SPM Physics video collection - Pelangi Multimedia Technologies Sdn. Bhd. (Selangor : Pelangi Multimedia Technologies Sdn. Bhd., 2006)
The SPM video coll ection is exclusively developed to instill the interest of physics in form 4 and form 5. This series can be used to provide extra information for those who wish to understand physics better
System requirements : Windows 98/Me/2000/XP, 128 RAM, hard disc space 16 MB, 16-bit sound card
Keywords: Physics -- Study and teaching (Secondary); Physics; Physical sciences